Opini Publik dan Kebijakan Pemerintah - Chatamallah, Maman (FIkom Unisba, 2007)
A reciprocal relationship exists between public opinion and government policy. Public opinion shaped and reshaped government policies, on the other hand, regulations also influence and transform the public. Public opinion could strengthen support to the administration. On the other hand, weak regulations would create unfavorable public opinion, which in turn will reduce people support toward the government. Such was the case of government policy over energy regulations in Indonesia. Unpopular decision to increase gasoline price made by Megawati administration turned out to be fatal when public opinion swung to another pole. From the image of the party for grass root, PDI then gained popularity as the party who betrayed and corrupted their constituents.